2017
DOI: 10.1038/s41598-017-05207-1
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelet Lysate versus Fetal Calf Serum: These Supplements Do Not Select for Different Mesenchymal Stromal Cells

Abstract: Culture medium of mesenchymal stromal cells (MSCs) is usually supplemented with either human platelet lysate (HPL) or fetal calf serum (FCS). Many studies have demonstrated that proliferation and cellular morphology are affected by these supplements – it is therefore important to determine if they favor outgrowth of different subpopulations and thereby impact on the heterogeneous composition of MSCs. We have isolated and expanded human bone marrow-derived MSCs in parallel with HPL or FCS and demonstrated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 29 publications
(42 reference statements)
2
61
1
1
Order By: Relevance
“…Unlike in other studies, here ASCs were expanded using human platelet lysate in the culture media, which may have the advantage of avoiding the use of animal‐derived factors. Human platelet lysate is widely used to grow MSCs, and many studies have demonstrated that this confers a degree of safety that is at least equivalent to that offered by fetal bovine serum . Indeed, some studies have suggested that the use of platelet lysate may increase cell yield and shorten the time for ex vivo expansion without epigenetic alterations …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike in other studies, here ASCs were expanded using human platelet lysate in the culture media, which may have the advantage of avoiding the use of animal‐derived factors. Human platelet lysate is widely used to grow MSCs, and many studies have demonstrated that this confers a degree of safety that is at least equivalent to that offered by fetal bovine serum . Indeed, some studies have suggested that the use of platelet lysate may increase cell yield and shorten the time for ex vivo expansion without epigenetic alterations …”
Section: Discussionmentioning
confidence: 99%
“…Human platelet lysate is widely used to grow MSCs, [23][24][25] and many studies have demonstrated that this confers a degree of safety that is at least equivalent to that offered by fetal bovine serum. 26,27 Indeed, some studies have suggested that the use of platelet lysate may increase cell yield and shorten the time for ex vivo expansion without epigenetic alterations. 25,27 One of the issues regarding the use of somatic cell medicinal products has been the selection of the cell dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells were isolated from the bone marrow of donors undergoing orthopedic surgery (n = 11; BM-MSC RWTH Aachen) (Fernandez-Rebollo et al 2017), from bone marrow aspirates of allogeneic hematopoietic stem cell donors (n = 8; BM-MSC University of Heidelberg) (Horn et al 2008), from subcutaneous adipose tissue lipoaspirates (n = 3, AT-MSC RWTH Aachen) (Cholewa et al 2011) and from umbilical cord pieces (n = 2; UCP-MSC; University of Hannover) (Selich et al 2016). Fibroblasts were isolated from dermis (n = 4; RWTH Aachen) (Koch et al 2012).…”
Section: Cell Culturementioning
confidence: 99%
“…Moreover, human PL preconditioned CD34+/CD133+-enriched bone marrow-derived progenitor cells were successfully used to improve vascularization in tissue-engineered constructs in vivo [25]. FernandezRebollo et al [26] strived to investigate the safety of human PL as a culture supplement and were able to show robust expansion of bone marrow-derived MSCs without significant changes in the DNA-methylation profiles, cytoskeletal organization, or focal adhesion. The supplementation with PL has been applied in a plethora of in vitro cell culture protocols.…”
Section: Prp and Pl As An Autologous Cell Culture Supplementmentioning
confidence: 99%